2019
DOI: 10.1002/jor.24512
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Producing Staphylococcus epidermidis (RP62A Strain) Inhibits Osseous Integration Without Osteolysis and Histopathology in a Murine Septic Implant Model

Abstract: Despite its presence in orthopaedic infections, Staphylococcus epidermidis's ability to directly induce inflammation and bone destruction is unknown. Thus, we compared a clinical strain of methicillin‐resistant biofilm‐producing S. epidermidis (RP62A) to a highly virulent and osteolytic strain of methicillin‐resistant Staphylococcus aureus (USA300) in an established murine implant‐associated osteomyelitis model. Bacterial burden was assessed by colony forming units (CFUs), tissue damage was assessed by histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Finally, this is the first work to describe direct S. agalactiae‐ mediated bone degradation, as evidenced by scalloping of bone. Previously described in S. aureus , but not in S. epidermidis infection, 51 the degradation of bone may release a nutrient source to the pathogen as well as expose extracellular matrix proteins for bacterial cell attachment and colonization 56 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, this is the first work to describe direct S. agalactiae‐ mediated bone degradation, as evidenced by scalloping of bone. Previously described in S. aureus , but not in S. epidermidis infection, 51 the degradation of bone may release a nutrient source to the pathogen as well as expose extracellular matrix proteins for bacterial cell attachment and colonization 56 …”
Section: Discussionmentioning
confidence: 99%
“…For S. aureus , it is understood that biofilm formation is a key survival mechanism in PJIs, as the biofilm provides protection from immune cell attack as well as resistance to antibiotic therapies 14,36,49,50 . In this model of osteomyelitis, both S. aureus and the less virulent Staphylococcus epidermidis 51 colonize the implant with approximately 10 4 CFUs at Day 14 post‐infection. Importantly, this study revealed that S. agalactiae does not persistently colonize the implant hardware, despite their known ability to form biofilms 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A constant 12‐h light/dark cycle was maintained. The murine implant‐associated tibial osteomyelitis model, which does not display sexual dimorphism, was used as previously described 10,21 . Briefly, a methicillin‐susceptible S. aureus (MSSA) strain (UAMS‐1) was cultured in tryptic soy broth (TSB) and used to contaminate a transtibial stainless‐steal implant with 2.5 × 10 5 colony‐forming unit (CFU) 22 .…”
Section: Methodsmentioning
confidence: 99%
“…The biofilm on the implant was assessed with SEM as a primary outcome (SEM: S‐4700; Hitachi Ltd.). The percent of the biofilm present on the 1 mm 2 region of interest (%biofilm area) was quantified with ImageJ (NIH) ( n = 5 in each group), as previously described 10,21 …”
Section: Methodsmentioning
confidence: 99%